Analisis Pengendalian Kualitas pada Engine Boss Drive Face K44F dengan Metode Six Sigma di PT. Sparta Guna Sentosa - Prima Fithri; Niffy Eri Yeni (Jurnal Optimasi Sistem Industri, 2016)
Industrial competition in Indonesia is getting strict. One of the important factor to win this competition is the quality level of the product produced. Production process in PT. Sparta Guna Sentosa generally produces defect products. Part that generate most of the defect products is Boss Drive Face K44F which the demand of this part for each period is high enough. Hence, the quality control using the Six Sigma method is needed to decrease the defect products. The Six Sigma is a method to analyzes the problem with DMAIC (Define, Measure, Analyze, Improve, and Control). The results showed that the main defect that will be priority of problem solving is the length which is below the specifications about 40 ~ 40.01 mm and then the solution of problem is designed.